Global-scale black carbon profiles observed in the remote atmosphere and compared to models - Schwarz, J; Spackman, J; Gao, R; Watts, L; Stier, P; Schulz, M; Davis, S; Wofsy, S; Fahey, D (American Geophysical Union, 2010)
Refractory black carbon (rBC) aerosol loadings and mass size distributions have been quantified during the HIPPO campaign above the remote Pacific from 80N to 67S. Over 100 vertical profiles of rBC loadings, extending from ~0.3 to ~14 km were obtained with a Single-Particle Soot Photometer (SP2) during a two-week period in January 2009. The dataset provides a striking, and previously unobtainable, pole-to-pole snapshot of rBC mass loadings. rBC vertical concentration profiles reveal significant dependences on latitude, while associated rBC mass size distributions were highly uniform. The vertical profiles averaged in five latitude zones were compared to an ensemble of AEROCOM model fields. The model ensemble spread in each zone was over an order of magnitude, while the model average over-predicted rBC concentrations overall by a factor five. The comparisons suggest that rBC removal in global models may need to be evaluated separately in different latitude regions and perhaps enhanced.